Nutritive capacity building in baby corn fodder through enhanced agronomic strategies - SHARMA, ARPITA; CHOPRA, N K; CHOPRA, NISHA K; KUMAR, RAKESH (The Indian Journal of Animal Sciences, 2019)
The knowledge of type of fodder/forages fed to animal is very important to determine how to best meet the amount of nutrients required for animal maintenance and production. The following study was undertaken to boost nutritive value of baby corn fodder. The primary objective of the study was to assess the amenable agronomic traits, viz. cultivars, sources of urea and nitrogen levels in manipulating the quality factors of baby corn fodder, viz. dry matter content, crude protein, ether extract, ash content, acid detergent fibre, dry matter intake, dry matter digestibility, neutral detergent fibre, net energy requirement, total digestible nutrients, relative feed quality and relative feed value. The experiment was piloted during 2016–17 and 2017–18 at research farm of Agronomy section, ICAR-National Dairy Research Institute, Karnal, India. The treatments consisted of two varieties of baby corn (PHM-1 and HM-4), four-coated urea (Neem coated urea, zinc coated urea, sulphur coated urea and prilled urea) and four nitrogen levels (180, 150, 120 kg N/ha and control). All the quality parameters of fodder improved with progression in dose of fertilizer nitrogen. The highest values of said indices were statistically cogent with application of nitrogen at level 180 kg/ha whereas, DM, NDF and ADF showed a significant reduction at 180 kg N/ha compared to control (no fertilizer applied). The baby corn fodder fertilized with nitrogen dose 180 kg/ha showed better crude protein content, had less fibre, improved dry matter digestibility and intake, more digestible nutrients and higher feed value and quality.